Prolonged Aftereffect of Visuomotor Adaptation to Gradually Distorted Reality Displayed on a See-Through Head-Mounted Device. Issue 15 (14th September 2019) - Kasuga, Shoko; Mori, Ryota; Kasahara, Shunichi; Rekimoto, Junichi; Ushiba, Junichi
ABSTRACT: Growing evidence suggests that the gradual transformation of visuomotor association drives a distinct learning process from abrupt transformation in humans. In the current study, we developed a novel omnidirectional visuomotor transformation paradigm to study details of such difference in more realistic environment than conventional experimental systems. Participants were asked to perform a repetitive three-dimensional (3D) arm-reaching task to a target on a front touch panel, wearing a video see-through head-mounted device that displayed a rotating view of surrounding images. In the abrupt condition, the images were rotated by 20°; in the gradual condition, the rotation was increased in a stepwise-manner from 0° to 20°. In both conditions, pointing errors were decreased after adaptation. Further, although the aftereffect of adaptation was not different between conditions, the speed of decay of the aftereffect, which was quantified by an exponential fit, was slower in the gradual condition, suggesting longer-lasting aftereffects for the gradual shift.